Pengaruh Literasi Keuangan, Motivasi Investasi, dan Locus of Control Terhadap Keputusan Investasi Mahasiswa Akuntansi - Felly Octaviani; Muhammad Fahmi; Helisa Noviarty (LPPM UBP, 2024)
In recent years, the interest in investment among young investors in Indonesia, especially those under the age of 30, has increased significantly. Nevertheless, low financial literacy remains a problem faced by many young people, which can pose risks to their investment decisions. This study aims to examine the influence of financial literacy, investment motivation, and locus of control on the investment decisions of accounting students. This research uses a quantitative approach with a survey method. The population of this study consists of accounting students from various universities in Indonesia. The sampling technique used is purposive random sampling, with a total of 100 respondents selected as the sample. Primary data was collected through the distribution of questionnaires, and data analysis was conducted using SPSS version 25 software. The results of the study indicate that financial literacy, investment motivation, and locus of control have a significant influence on investment decisions